Bibliometric Analysis using Vos Viewer with Publish or Perish of Intelligent Tutoring System in Private Universities - Kurniawan, Bobi; Meyliana, M; Leslie Hendric Spits Warnars, Harco; Suharjo, Bambang; Ahiase, Godwin (Universitas Komputer Indonesia, 2024)
The objective of this study is to analyze the development of intelligent tutoring systems in private universities. We conducted the analysis using bibliometric methods, utilizing the Publish or Perish and VOSviewer applications. Data was obtained by using the publish or perish application with the keyword